Dancing as an Intervention Tool for People with Dementia: A Mini-Review Dancing and Dementia - Klimova, Blanka; Valis, Martin; Kuca, Kamil (Current Alzheimer research, 2017)
BACKGROUND: Research studies show a positive impact of physical activities such as dancing on the improvement of cognitive reserves of people with dementia. OBJECTIVE: The purpose of this study is to explore dancing efficacy on people with dementia and list the key benefits and limitations of dancing therapy for these people. METHODS: The methods used in this study include a method of literature review of available Englishwritten sources with respect to the dancing therapy and dementia in the acknowledged databases Pub- Med, Web of Science, Springer, and Scopus, and a method of comparison and evaluation of their findings. RESULTS: The findings of this mini review confirm positive efficacy of dancing therapy on cognitive, physical, emotional and social performance of people with dementia. CONCLUSION: More randomized controlled clinical trials should be conducted in this field, as well as other non-pharmacological therapies should be employed in order to holistically contribute to the prevention and treatment of dementia.
Keywords: findings; limitations; benefits; dancing; Dementia; Humans; review.; lidé; cvičení; efficacy; Dance Therapy; Exercise; demence; terapie tancem